Microfiltration membrane processes: A review of research trends over the past decade - Nidal Hilal (Journal of Water Process Engineering, 2019)
Since its inception in the 19th century, microfiltration (MF) has evolved as a membrane-based separation technology for treating various effluents and wastewaters. This review aims to familiarize its readers with general and specific research trends on various topics in MF. The level of research interest has been measured by the number of publications in that area for each year. An increasing research trend was observed from the number of publications since 2009 to 2018 with MF as the major topic. During the past decade, MF articles have spanned in about 150 different journals, with The Journal of Membrane Science, Desalination and Separation and Purification Technology being the major ones. Major topics of interest include membrane fabrication and modification, waste water treatment and fouling studies, while a significant research increase was seen in various fabrication methods and MF application in the food sector. MF modeling still remains a topic which needs further research output, and has experienced a decline over the past years. Several potential research areas are also identified in this review which will help future researchers to materialize their efforts into the right direction.